Функційно-семантичне навантаження периферійних онімів роману Валерія Шевчука «Стежка в траві» - Скорук, Ірина; Skoruk, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглянуто особливості периферійного онімного простору роману Валерія Шевчука «Стежка в траві». Проаналізовано функційну специфіку кожного з використаних автором онімних класів та визначено їх структурно-семантичні особливості. З’ясовано роль поетонімів у розвитку сюжету, в побудові мовної та літературної композиції твору. Звернено увагу на особливості індивідуально- авторського стилю Валерія Шевчука, що виявлені в системі онімного простору роману «Стежка в траві». The article reveals the features of peripheral proper nouns in Valery Shevchuk’s novel «A Path in the Grass». Among the peripheral onyms the author highlighted theonyms, mifonyms, ideonyms, ergonyms, names of animals and other onomastic ranks that confer artistic text expressive-stylistic and artistic coloring. The article analyzes the functional specificity of each of the onymastic classes used by the author and identifies their structural and semantic features. In the focus of attention is their semantic loading, their quantitative and qualitative meanings. The article offers perspective vectors of the problem development aimed at revealing functional role of proper names in the story. The author states that created by the writer and being used in the text, they form special onomastic stylistically expressive literary text. The author draws the conclusions as to the contextual role of onyms, their emotional expressive meaning and comment on their symbolic function and also the role of occasional onyms in creating individual author’s writing style. Metaphorization of abstract concepts expresses the inner world of the characters and enriches the emotional context of the text.
Functional and Semantic Loading of Peripheral Onyms in Valery hevchuk’s Novel «A Path in the Grass»
Keywords: онім; онімний простір; поетонім; функційно-семантичне навантаження; proper name; the space of proper names; the sphere of proper names; functional and semantic peculiarities